Fairness and rights in international criminal procedure - Rigney, Sophie (Edinburgh : Edinburgh University Press, 2022)
Through an in-depth critical analysis of procedural decisions at the ICTY and ICC between 2008 and 2018, Rigney shows that there is a clear separation between fairness and rights in practice. She demonstrates tthat fairness is invoked in international criminal law decisions in inconsistent ways that are frequently at odds with defendants' rights.
Title from publisher's bibliographic system (viewed on 18 Nov 2022).
Keywords: Criminal procedure (International law); International criminal courts